The Local Impact on the Concurrent Sentiment-Return Nexus: Asian versus European Markets - Ngoc Bao Vuong; Yoshihisa Suzuki; Anh Tho To (Ital Publication, 2021)
We examine the relationship between investor sentiment and contemporaneous returns in sixteen Asian and European stock markets between 2004 and 2016. To identify the sentiment-return nexus, we use the OLS models with Newey-West standard errors as well as the panel regressions with cross-country fixed effects and time dummies. We report the regional outcomes for Asia, Europe, and the individual markets. Our empirical results reveal a significant effect of sentiment on stock returns, although those effects are nonidentical across markets. We find the dissimilarities in the sentiment-return relationship among the sample markets are driven negatively by almost all national factors, with the strongest determinants being the development of financial institutions and the quality of regulation. The impact of cultural dimensions among the sample markets, on the contrary, is relatively weak and mixed. Our research is the first to compare Asian and European outcomes and reveal which region is more vulnerable to the influence of the local components. We detect that, except cultural aspects, European markets are more sensitive to country-specific characteristics than Asian ones. Doi: 10.28991/esj-2021-01318 Full Text: PDF